Optical coherence contrast imaging using gold nanorods in living mice eyes. (12th February 2015) - de la Zerda, Adam; Prabhulkar, Shradha; Perez, Victor L; Ruggeri, Marco; Paranjape, Amit S; Habte, Frezghi; Gambhir, Sanjiv S; Awdeh, Richard M
Abstract Background Optical coherence tomography (OCT) is a powerful imaging modality to visualize tissue structures, with axial image pixel resolution as high as 1.6 μm in tissue. However, OCT is intrinsically limited to providing structural information as the OCT contrast is produced by optically scattering tissues. Methods Gold nanorods (GNRs) were injected into the anterior chamber (AC) and cornea of mice eyes which could create a significant OCT signal and hence could be used as a contrast agent for in vivo OCT imaging. Results A dose of 30 nM of GNRs (13 nm in diameter and 45 nm in length) were injected to the AC of mice eyes and produced an OCT contrast nearly 50‐fold higher than control mice injected with saline. Furthermore, the lowest detectable concentration of GNRs in living mice AC was experimentally estimated to be as low as 120 pM. Conclusions The high sensitivity and low toxicity of GNRs brings great promise for OCT to uniquely become a high‐resolution molecular imaging modality.